(untitled) (Scientific journal of the Fergana State University, 2026)
This study presents data on the distribution, ecological features, and diagnostic characteristics of predatory bugs (Reduviidae) in the Fergana Valley. Empicoris vagabundus, Reduvius personatus, Zelus renardii were recorded for the first time in the region’s fauna. The results highlight the significant role of Reduviidae species as natural predators contributing to biological control within agricultural ecosystems.